Diseño de mapa urbano de zonificación geotécnica del área oriental de la comuna cuatro, Duitama - Rosas Valderrama, Oscar Francisco (Universidad Antonio Nariño, 2023)
This graduation Project has like an object desaing a map to geotechnical zoning, which is to be carried out in the eastern part of commune 4 in the city of Duitama, Boyaca All of this taking into consideration the information available from the databases of the municipal administrative entities and the soil studies that include the phreatic level, bearing capacities, type of soil, geology, geomorphology, cadastral base and map of the city communes. In this order of ideas, it was carried out, through an experimental methodology, data collection, sources of secondary information and sampling in the field in order to establish the geotechnical characteristics of the area of influence using the application of GIS tools and the ArcGIS Kriging interpolation method that allowed establishing an indicator of the bearing capacity in areas where this information was not available Consequently, it was evidenced that the application is viable of GIS tools for the design of geotechnical categorization maps at the micro level, in accordance with the results obtained and the comparison made with the field surveys, it is evident that the study area has an optimal bearing capacity, which makes future investors minimize costs in foundation activities.